The effect of perceived service recovery justice on customer loyalty: role of customer affection as moderator in Malaysian telecommunication industry / Siti Aisyah Yaakob …[et al.] - Yaakob, Siti Aisyah; Mohamad, Nur Syaahidah; Mohd Ghani, Nur Nashreena Aliya; Abd Rahman, Nur Ain; Othman, Abdul Kadir (Faculty of Business and Management and UiTM Press Universiti Teknologi MARA, Malaysia., 2017)
Customer loyalty has been the goal of service providers including telecommunication companies. They need to make sure that they can retain their customers as long as possible. Service recovery is one of the aspects that should be focused on as telecommunication services tend to receive a lot of complaints from the users. The ability of service providers to handle and solve all the problems appropriately will provide justice to their customers. Previous studies found the link between customer affection and loyalty which indicates its importance to strengthen the emotional tie between customers and companies after service recovery. Therefore, this study is intended to examine the moderating effect of customer affection on the link between service justice and customer loyalty. An analysis of 100 data using multiple regression analysis revealed that procedural justice is significant to influence customer loyalty. This finding indicates that telecommunication companies should pay attention on procedural justice in performing their service recovery. The results also found that customer affection does not significantly moderate the relationship between service justice and customer loyalty.